The potential scalability of High-pressure sliding technique for developing ultrafine grained material with enhanced mechanical properties of AA7075 - Eman M. Zayed; Mostafa Shazly; Ahmed El-Sabbagh; Nahed A. El-Mahallawy (Heliyon)
High-pressure sliding (HPS) is one of severe plastic deformation (SPD) methods that is utilized for significant grain refinement and it is similar to high-pressure torsion (HPT) as both processes are operated under high pressure. Whereas the HPT process uses small disk-shaped samples, the HPS process is applicable for larger samples. This study introduces an enhanced modification of the HPS process named as the Multi-Pass Incremental Feeding HPS (MPIF-HPS). It aims to enlarge the processed sample dimensions to 4X120X10 mm. The MPIF-HPS process is applied up to 4 passes to aluminum 7075 confined flat samples to achieve superior properties under a controlled pressure in the range of 15–50 GPa. This pressure range increases with each successive pass due to the strain hardening effect. The process involves an incremental sliding distance of 5 mm along the deformed length at room temperature. The average grain size decreased with increasing the number of passes and reached ∼200 nm after the fourth pass, with an increase in both ultimate tensile strength and ductility. The ultimate tensile strength and % elongation reached 650 MPa and 22 %, with improvement of 44 % and 56 % respectively. A finite-element method (FEM) was used to simulate the magnitude of the strain including its distribution on the cross section of the sheet through processing by HPS. It was demonstrated that strain and hardness homogeneity was developed in the sheet processed by the MPIF-HPS after the forth pass. The utilization of Electron Backscatter Diffraction (EBSD) provided crucial insights into microstructural evolution and determination of grain size in SPD-processed samples. These findings show that the MPIF-HPS process holds a considerable potential for scaling up the process to accommodate larger sample sizes and diverse cross-sections. Based on these results, this technique proves a good potential for scalability of the HPS process to larger sample sizes and various cross-sections.